Development of enzymatic pretreatment of palm oil mill effluent for monomers towards biogas production - Islam, MS Tajul; Alam, Md. Zahangir; Mamun, Abdullah Al; Elgharbawy, Amal A.; Riyadi, Fatimah Azizah (Penerbit Akademia Baru, 2017)
In anaerobic digestion for enhancement of biogas production, various types of pre-treatment method have been used with some limitations in terms of sustainable environmental management. Although acid and alkali pretreatment have a significant effect on the degradation of biomass, these methods have some negative impacts on the environment due to their hazardous nature, while the enzymatic pre-treatment is more environmentally friendly. One of the constraints of using the enzyme in pretreatment process for biogas production is a high cost which is currently focused to reduce cost through using a locally produced enzyme. The hydrolytic enzymes, cellulase and lipase were applied to evaluate the pretreatment and hydrolysis process for POME based biogas production. The results showed that about 66.67% more free fatty acid (FFA) was obtained in this study in compared to untreated sample as the control (POME) by using 15 U/ml lipase at the pH of 4.5. About 3 fold higher reducing sugar was recorded at the loading of 2.4 FPU/ml cellulase enzyme as compared to the control at the pH range 4. Both enzymes were effective in the pretreatment process in conversion of complex substances in the POME into monomars towards biogas production.